On sealing effects and oxygen dependence of non-recoverable intensity drops in short-chain-conjugated polymers - White, J (2002)
The fluorescence time trace of persistent length single poly (2,5-dioctyloxy p-phenylene vinylene) (DOO-PPV) polymers spin-cast in an inert matrix is recorded under different sealing conditions-which effectively results in different levels of oxygen exposure. The frequency of non-recoverable intensity drops is seen to be dependent on oxygen concentration. Qualitative differences in published results for the photophysics of long-chain polymers and rod-like polymers are shown to be due to chain length differences and not due to sealing conditions. (C) 2002 Elsevier Science B.V. All rights reserved.